Effectiveness of Homoeopathy in Myocardial Infarction (MI) (Homoeopathy for All, 2025)
Cardiovascular diseases fall under  major cause of morbidity and  mortality and is considered a rapidly  growing problem worldwide. It  is estimated that over 40 million  Indians have some kind of cardio  vascular diseases.  The symptom  manifest most often as chest pain  or chest discomfort. The best  way to reduce the incidences of  cardiac diseases is by avoiding or  minimizing the risk factors that  triggers the disease.  The efforts to  control life style diseases which are  major risk factors for cardio vascular  diseases will definitely contribute  to the cardio vascular disease  prevention.  Homeopathy offers a  significant complementary role in  the management of cardiovascular  diseases, can be either preventive,  curative or palliative. Materia  medica has number of medicines  that could be effective in managing  the cases of MI. It is proved helpful  in eliminating the risk factors,  preventing the progress of disease,  and preventing sudden death  and morbidity due to myocardial  ischemia.
Keywords: Angina; myocardial infarction; ECG; Homoeopathy etc